THE EVOLUTION OF DIGITAL INTELLIGENCE IN EDUCATION - Loso Judijanto; Agustin Nurya Savitri; Eyad Saleh Bani-Domi (Adisam Publisher, 2025)
In recent years, digital intelligence has developed significantly and plays an important role in the transformation of education. The research method conducted in this study is literature. The results show that advances in educational technology such as AI, VR, and the use of big data have provided innovative instruments to facilitate a learning process that is more of being split into autonomous and specialised. The adoption of these new tools seems to increase interaction and personalization in learning, providing opportunities for students to learn at their own time and pace. However, the literature also notes the challenges faced, including unequal access to technology, the need for infrastructure adaptation, and the demand for teacher capacity building. The results show that students who have complete and supportive access to digital intelligence show improvements in academic engagement and achievement.